MENINGKATKAN PENGETAHUAN MASYARAKAT TERHADAP PERBAIKAN SANITASI LINGKUNGAN DI DESA TUPABBIRING - Rahmat Nurhidayat (Pangulu Abdi: Jurnal Pengabdian Kepada Masyarakat, 2023)
This research is entitled "Increasing Community Knowledge of Environmental Sanitation Improvement in Tupabbiring Village." The researcher is interested in raising this title because in this village environmental sanitation is still one of the problems that must be resolved. The negative impact of environmental sanitation is more dominant than the positive impact or even said to have no positive impact at all. Because the risk of environmental sanitation has a negative impact on society, especially children who are vulnerable to dengue fever and stunting, and food that comes from rivers cannot be consumed. The negative impact of environmental sanitation can also have an impact on the environment. Efforts that can prevent an increase in Environmental Sanitation are empowering with information, educating and providing insight to the community to create a good environment. Keywords: Impact of environmental Sanitation; Prevention; Extension; Environmental Sanitation.